Effectiveness of micronutrients in the improvement of seed yield and quality of coriander cv.CO4 - Kapoor, Atal Chanaya; Mukesh, Bhagat; Sen, Ranbir Ray (Global Journal of Food and Agribusiness Management, 2017)
The field experiments were conducted during two seasons to find out the role of micronutrients on growth, seed yield and quality in coriander cv. CO4. The soil of the experimental site was calcareous. Micronutrient deficiencies are common in soils that have a high calcium carbonate (CaCO 3) due to reduced solubility at alkaline pH values. Micronutrients such as iron (Fe), zinc (Zn), copper (Cu) and manganese (Mn) were applied in their sulphate form (FeSO4, ZnSO4, CuSO 4 and MnSO4, respectively). The effect of both soil application (25 kg/ha) and foliar spray (0.5%) of micronutrients at 30 and 45 days after sowing were studied individually. Foliar spray of 0.5% FeSO4 induced the highest growth rates in terms of net assimilation rate (0.085 mg g-1 day-1 in rabi and 0.063 mg g-1 day-1 in kharif) and crop growth rate (7.52 mg m-2 day-1 in rabi and 7.78 mg m-2 day-1 in kharif). Maximum number of umbels per plant (33.7 in rabi and 13.8 in kharif) and highest seed yield per hectare (623.3 kg in rabi and 599.9 kg in kharif) were observed for the foliar application of 0.5% FeSO4 if compared to other treatments. Foliar application of iron and zinc exhibited significant effect on resultant seed quality parameters. The study revealed the need for application of micronutrients in maximum realization of yield and quality of the coriander seed crop in calcareous soils